PLATE WITH THE IMAGE OF THE HORSEMAN FROM NYALINSK-1 FORT - A. V. Novikov; I. P. Zakharova (Вестник Кемеровского государственного университета, 2015)
The terne plates with repoussed images of different themes are very rare findings in the north of Western Siberia and represent a specific and independent phenomenon. The plate with the image of the horseman was found at the Nyalinsk-1 fort (KhMAD-Yugra) in 2006. It is an object of Russian native arts and crafts, which which was intended for realization among the aboriginal people of Western Siberia. The paper provides a detailed description of the image on the plate and offers the variants of the theme interpretations. More than likely, the image of the rider on the horse is associated with the tradition of Russian Orthodox arts, and the plate appeared in the north of Western Siberia due to Christianization at this territory. Probably, the fort represents the Khanty sacrarium, and the plate appeared there as a result of oblation. The dating of the plate is discussed and the most probable variant supposes that it relates to the 16th – 17th centuries. The plate could have been made in one of the trade centres in the East European part of Russia and taken to the West Siberian territory. But its local (Siberian) origin in the forming Russian trade community is possible.